Potential benefit of Pentraxin 3 use as inflammatory marker in gynecological and obstetric diagnostics - Anna Moskalonek; Wioletta Mikołajek-Bedner; Karolina Nurek; Dorota Torbé; Andrzej Torbé (Kazimierz Wielki University, 2019)
Pentraxin 3 (PTX3) belongs to the PTX family, which is represented by the short and long arm proteins. Classified as an acute-phase inflammatory response marker, it plays its role in innate immunity. Being produced by macrophages, monocytes, dendritic cells and even tissue cells, it has shown to be one of the most significant indicators of every progressing infection. Certain increased levels of PTX3 have been successfully marked in many disorders and pathologies, giving a powerful feedback in hematology, neurology, as in many cardiovascular, respiratory and inflammatory cases as well. In this review we tried to bring closer the potential of PTX3 usage and underline its possible positive input in the diagnostic phase of the gynecological and obstetric emergencies, based on most recent available researches.